Management of business processes in logistical networks of the food supply chain - Velychko, O.; Величко, Олександр Петрович; Velychko, L.; Величко, Л. А.; Berezhetska, S.; Бережнецька, С. Ю. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2020)
The logistics strategy of building business processes is an essential component of efficient management in the food supply chain under contemporary conditions. It is to provide appropriate availability of the goods while transporting them to the sales market. Owing to the sales intemrediaries, it is possible to reduce the number of direct contacts of producers with consumers of the produce. The features of management in operational process within the sales logistics systyem have been considered. The method of the research is the development of logistic networks and designing decisions aimed at their optimization under the conditions of the trade -intermediary activity at the foodstuffs market. The methodological component of the research is focused on the integrated application of rationalistic and providing logistics concepts, criteria analysis, linear programming and logistical modeling. The material of the research was chosen a set of trade-intermediary organizations, which work at the market of foodstuffs in Central and Eastern areas of Ukraine. Transformation of the known information from the operational management to new objects in the system of trade foodstuffs logistics had further development. Integrated methodical approaches to projecting rational decisions in the area of managing logistics of distribution have been grounded. The ways of optimizing the supply process and transportation at goods distribution by distribution channels have been grounded. Preconditions to efficient management over supply chain in the system of trade logistics have been generalized. Application of the method of the transportation task while projecting the managerial decision on the optimal plan of foodstuffs transportation makes possible to determine the content and the quantity of the goods which can reasonable be supplied to residential areas of the city. The suggested logistical model additionally provides optimal distribution of goods by distribution channels considering the main factors which influence the efficiency of food supply chain management. The value of the obtained research results can be seen as the development of possibilities for efficient management over the logistics networks in the system of the trade logistics. The developed recommendations can be used by trade-intermediary organizations for managing food supply chain. У сучасних умовах логістична стратегія побудови бізнес-процесів є важливою складовою ефективного управління продовольчим ланцюгом постачання. Вона має забезпечувати належну доступність товару при прямуванні його до ринку збуту. За допомогою торговельних посередників можна скоротити кількість прямих контактів виробників із споживачами продукції. У статті розглянуто особливості менеджменту операційних процесів в системі торговельної логістики. Метою дослідження є розвиток логістичних мереж та проектування рішень щодо їх оптимізації в умовах торговельно-посередницької діяльності на ринку продовольчих товарів. Методологічна складова дослідження зорієнтована на інтегроване використання положень концепції раціоналістичної та забезпечувальної логістики, критеріального аналізу, лінійного програмування, а також логістичного моделювання. Матеріалами для досліджень було обрано низку торговельно-посередницьких організацій, які працюють на ринку продовольчих товарів у Центральному та Східному регіонах України. Дістало подальшого розвитку перенесення відомих знань із операційного менеджменту на нові об’єкти в системі торговельної логістики продовольчих товарів. Обгрунтовано інтегровані методичні підходи до проектування раціональних рішень в середовищі управління логістикою дистрибуції. Запропоновано шляхи оптимізації процесу управління постачанням та транспортними перевезеннями при розподілі продукції за каналами реалізації. Узагальнено передумови ефективності управління ланцюгом постачання в системі торговельної логістики. Застосування методу транспортної задачі при проектуванні управлінського рішення щодо оптимального плану перевезень продовольчої продукції дозволяє встановити із якого складу і яку кількість продукції найбільш доцільно транспортувати у житловий район міста. До того ж часу запропонована логістична модель додатково забезпечує оптимальний розподіл продукції за каналами реалізації із урахуванням основних чинників впливу на ефективність управління продовольчим ланцюгом постачання. Цінність одержаних результатів дослідження полягає у розвитку можливостей для ефективного управління логістичними мережами в системі торговельної логістики. Розроблені рекомендації можуть бути використані торговельно-посередницькими організаціями в управлінні продовольчим ланцюгом постачання.
Управління бізнес-процесами у логістичних мережах продовольчого ланцюга постачання
Величко О. П. ORCID: 0000-0003-2700-0329 ; Величко Л. А. ORCID: 0000-0002-8255-8774 ; Бережнецька С. Ю. ORCID: 0000-0002-6082-8673
Keywords: logistics; логістика; management; менеджмент; trade; торгівля; optimization; оптимізація; operations; операції; distribution; дистрибуція; supply; постачання; transportation; транспортування; food; продовольство